Analisis Kemampuan Literasi Matematika Siswa Terhadap Pengembangan Pendidikan Karakter Menuju Profil Pelajar Pancasila - Ley Leana, Kunthy; Firdaus, Andi Mulawakkan (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
This research aims to: 1) describe students' mathematical literacy abilities in block material towards the development of character education towards the Pancasil Student Profile. 2) Describe the factors that influence students' mathematical literacy skills in block material towards the development of educational character towards the Pancasil Student Profile. This research method is qualitative. The subjects in this research were students of class VII-1, class VII-2, class VII-3 at SMP Negeri 2 Sungguminasa. Data collection instruments used learning independence questionnaires, mathematical literacy ability tests, and interview sheets. The data analysis used in this research is qualitative descriptive analysis. namely, data reduction, data presentation, and drawing conclusions. The results of the research show that 1) Students' mathematical literacy skills towards developing high learning character education have an average of 75.45 (high category). Most students are not capable at the reasoning and argumentation stage. 2) students' mathematical literacy skills towards developing character education who are currently studying have an average of 60.32 (medium category), most of whom are unable to design strategies to solve problems. 3) students' mathematical literacy skills towards the development of low learning character education have an average of 39.08 (low category) most of them are not capable at the mathematics stage. 4) factors that influence mathematical literacy skills on the development of learning character education in block material are generally influenced by internal factors, namely factors from the students themselves, namely the lack of ability to understand, accept, or digest the subject matter, students have difficulty in making strategies in solving problems using good in using the formula that will be used, operating rules, does not provide the correct steps in answering the question.